Сyclotron wave absorption in large aspect ratio elongated tokamaks - Grishanov, N.I.; Azarenkov, N.A. (Вопросы атомной науки и техники, 2013)
Transverse dielectric susceptibility elements are derived for radio frequency waves in a large aspect ratio toroidal plasma with elliptic magnetic surfaces by solving the Vlasov equation for untrapped, t-trapped and d-trapped particles. These dielectric characteristics are suitable for estimating the wave absorption by the fundamental cyclotron resonance damping in the frequency range of ion-cyclotron and electron cyclotron resonances.